Complete Genome Sequence and Biodegradation Characteristics of Benzoic Acid-Degrading Bacterium Pseudomonas sp. SCB32. (3rd July 2020) - Xiang, Wei; Wei, Xiaolan; Tang, Hui; Li, Liangbo; Huang, Rongshao
Abstract : Allelochemicals are metabolites produced by living organisms that have a detrimental effect on other species when released into the environment. These chemicals play critical roles in the problems associated with crop replanting. Benzoic acid is a representative allelochemical found in root exudates and rhizosphere soil of crops and inhibits crop growth. The bioremediation of allelochemicals by microorganisms is an efficient decontamination process. In this research, a bacterial strain capable of degrading benzoic acid as the sole carbon source was isolated. The genome of the strain was sequenced, and biodegradation characteristics and metabolic mechanisms were examined. Strain SCB32 was identified as Pseudomonas sp. based on 16S rRNA gene analysis coupled with physiological and biochemical analyses. The degradation rate of 800 mg L -1 benzoic acid by strain SCB32 was greater than 97.0% in 24 h. The complete genome of strain SCB32 was 6.3 Mbp with a GC content of 64.6% and 5960 coding genes. Potential benzoic acid degradation genes were found by comparison to the KEGG database. Some key intermediate metabolites of benzoic acid, such as catechol, were detected by gas chromatography-mass spectrometry. The biodegradation pathway of benzoic acid, the ortho pathway, is proposed for strain SCB32 based on combined data from genome annotation and mass spectrometry. Moreover, the benzoic acid degradation products from strain SCB32 were essentially nontoxic to lettuce seedlings, while seeds in the benzoic acid-treated group showed significant inhibition of germination. This indicates a possible application of strain SCB32 in the bioremediation of benzoic acid contamination in agricultural environments.